Cytokine responses in birds challenged with the human food-borne pathogen Campylobacter jejuni implies a Th17 response. Issue 3 (March 2016) - Reid, William D. K.; Close, Andrew J.; Humphrey, Suzanne; Chaloner, Gemma; Lacharme-Lora, Lizeth; Rothwell, Lisa; Kaiser, Pete; Williams, Nicola J.; Humphrey, Tom J.; Wigley, Paul; Rushton, Stephen P.
Abstract : Development of process orientated understanding of cytokine interactions within the gastrointestinal tract during an immune response to pathogens requires experimentation and statistical modelling. The immune response against pathogen challenge depends on the specific threat to the host. Here, we show that broiler chickens mount a breed-dependent immune response to Campylobacter jejuni infection in the caeca by analysing experimental data using frequentist and Bayesian structural equation models (SEM). SEM provides a framework by which cytokine interdependencies, based on prior knowledge, can be tested. In both breeds important cytokines including pro-inflammatory interleukin (IL)-1β, , IL-4, IL-17A, interferon (IFN)-γ and anti-inflammatory IL-10 and transforming growth factor (TGF)-β4 were expressed post-challenge. The SEM revealed a putative regulatory pathway illustrating a T helper (Th)17 response and regulation of IL-10, which is breed-dependent. The prominence of the Th17 pathway indicates the cytokine response aims to limit the invasion or colonization of an extracellular bacterial pathogen but the time-dependent nature of the response differs between breeds.